Peran Transformasi Digital Bagi Keberlanjutan Usaha Mikro Di Era Modern - Novelia Utami; Nadila Oktaviani; Siti Rohaeni; Vina Yuliyana (CV. ITTC INDONESIA, 2024)
Digital transformation has become the main key in increasing the competitiveness and continuity of micro businesses amidst increasingly fierce global competition. This article outlines how micro-enterprises can leverage digital technology to optimize their business processes, increase operational efficiency, and achieve a wider market share through online platforms. Digital transformation allows micro businesses to adopt various technologies such as e-commerce, digital marketing, data analytics, and cloud computing. This approach not only facilitates cost and time efficiencies, but also allows microenterprises to access resources and markets that they previously could not reach traditionally. Digital transformation also has the potential to improve environmental sustainability by reducing carbon footprints through reduced paper and energy use. However, the challenges faced by micro-enterprises in adopting digital technologies are also discussed, including access limitations, required skills, and data protection and privacy. This article underscores the importance of appropriate policy support and government initiatives to facilitate the transition of microenterprises to the digital economy. Thus, digital transformation is not only about adopting new technologies, but also about changing business paradigms to achieve long-term sustainability of micro-enterprises in the modern era. The results of the assistance provided by the research were designing and printing menu lists, designing and printing banners, designing and printing sticker logos, registering and printing QRIS for non-cash payments, making promotional videos, and registering Shopeefood.